Antimicrobial Resistance in the Context of Animal Production and Meat Products in Poland—A Critical Review and Future Perspective - Patryk Wiśniewski; Miłosz Trymers; Wioleta Chajęcka-Wierzchowska; Katarzyna Tkacz; Anna Zadernowska; Monika Modzelewska-Kapituła (Pathogens)
The prevalence of antimicrobial-resistant bacteria in meat and meat products is a significant public health challenge, largely driven by the excessive and inappropriate use of antimicrobials in animal husbandry. In Poland, a key meat producer in Europe, antibiotic-resistant pathogens such as Campylobacter spp., Staphylococcus spp., Enterococcus spp., Listeria monocytogenes, and Enterobacterales have been detected in meat, posing serious risks to consumers. This review examines the use of antimicrobial agents in meat production and the resulting antimicrobial resistance (AMR) in microorganisms isolated from meat products in Poland. The mechanisms of AMR, genetic factors, and prevalence in Poland are presented. It highlights key factors contributing to AMR, such as antibiotic misuse in livestock farming, and discusses the legal regulations governing veterinary drug residues in food. This review emphasizes the importance of monitoring and enforcement to safeguard public health and calls for further research on AMR in the meat industry. Antimicrobial resistance in meat and meat products in Poland is a huge challenge, requiring stricter antibiotic controls in animal husbandry and improved surveillance systems. Additionally, the impact of husbandry practices on the environment and food requires further research. Future efforts should focus on nationwide monitoring, alternative strategies to reduce antibiotic use, and stronger enforcement to combat antimicrobial resistance and protect public health.